UKURAN LAYAK TANGKAP IKAN PELAGIS KECIL DI PERAIRAN KENDARI, SULAWESI TENGGARA - Heri Widiyastuti; Herlisman Herlisman; Andina Ramadhani Putri Pane (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
The small pelagic resources in the waters of Kendari (FMA 714) that are dominant are mackerel scad (Decapterus macarellus) and Indian mackerel (Rastrelliger kanagurta). Fishing in these waters uses a mini purse seine, with the production of 2 species of fish has reached 38.2% of the total allowed catch FMA 714. Because of intensive use, management needed to preserve resources. The purpose of this study is to determine the decent size based on a comparison of length of the first capture (Lc) and the length of first mature (Lm), and prediction of spawning season. Data collection was conducted by researchers and assisted by enumerators monthly. The results showed that the size of the mackerel scad in between 17.5 - 30.5 cm FL (n = 3207 tails). The size of the Indian mackerel found between 18.5 - 26.5 cm FL (n = 2556). The length at first captured of both species was larger than the size at first matured (Lm> Lc) so that the decent size is 23 cm FL for mackerel scad and 22 cm FL for Indian mackerel. The prediction of the spawning season in May-August can be the basis for closing the area during the spawning season. Keywords: : mackerel scad, Indian mackerel, mini purse seine, decent size, FMA 714